The internal migration between public and faith-based health providers: a cross-sectional, retrospective and multicentre study from southern Tanzania - Tabatabai, Patrik; Prytherch, Helen; Baumgarten, Inge; Kisanga, Oberlin M. E.; Schmidt-Ehry, Bergis; Marx, Michael (Tropical medicine & international health, 2013)
Objective To assess the magnitude, direction and underlying dynamics of internal health worker migration between public and faith-based health providers from a hospital perspective. Methods Two complementary tools were implemented in 10 public and six faith-based hospitals in southern Tanzania. A hospital questionnaire assessed magnitude and direction of staff migration between January 2006 and June 2009. Interviews with 42 public and 20 faith-based maternity nurses evaluated differences in staff perspectives and motives for the observed migration patterns. Results The predominant direction of staff movement was from the faith-based to the public sector: 69.1% (n = 105/152) of hospital staff exits and 60.6% (n = 60/99) of hospital staff gains. Nurses were the largest group among the migrating health workforce. Faith-based hospitals lost 59.3% (n = 86/145) of nurses and 90.6% (n = 77/85) of registered nurses to the public sector, whereby public hospitals reported 13.5% (n = 59/436) of nurses and 24.4% (n = 41/168) of registered nurses being former faith-based employees. Interviews revealed significantly inferior staff perspectives among faith-based respondents than their public colleagues. Main differences were identified regarding career development and training, management support, employee engagement and workload. Conclusion This study revealed considerable internal health worker migration from the faith-based to the public sector. Staff retention and motivation within faith-based hospitals are not restricted to financial considerations, and salary gaps can no longer uniquely explain this movement pattern. The consequences for the catchment area of faith-based hospitals are potentially severe and erode cooperation potential between the public and private health sector.
Gesehen am 27.01.2022